The Improvement of Germination of some Forest Species by Acid Scarification - Zodape, Sudhakar T. (Indian Forester, 1991)
The germination of some of the economically Important species like Acacia nilotica, Acacia Lecophloea, Albizia lebbek, Bauhinia racemosa, Dichrostachys cinerea, Haematoxylon campochianum,Leucaena leucacephala, Parkisonia acileata and Peltaphorum preprocarpum was studied. The seeds were collected from Victoria Park. BhAvnagar in 1982. Difrerent soaking periods Were given depending on tbe nature of tbe seedcoat. The shortest duration of the treatment i.e 8 minutes was given to the Haemaroxylon campachianum where as longer duration i.e. upto 60 minutes treatment Was given to the seed of Acacia nilorica. In all tbe studied species, acid scariflication to the seeds gave significant increase in percentage germination over the contro. Hundred percent germination against the control germination percentage of zero and 25% was achived in case of Bauhin recemosa and Parkisonia aculenta, when the sees were soaked in concetrated H2So4 fo 30 minutes respectively.